Biodiversity and vector‐borne diseases: Host dilution and vector amplification occur simultaneously for Amazonian leishmaniases. Issue 8 (21st January 2022) - Kocher, Arthur; Cornuault, Josselin; Gantier, Jean‐Charles; Manzi, Sophie; Chavy, Agathe; Girod, Romain; Dusfour, Isabelle; Forget, Pierre‐Michel; Ginouves, Marine; Prévot, Ghislaine; Guégan, Jean‐François; Bañuls, Anne‐Laure; et al.
Abstract: Changes in biodiversity may impact infectious disease transmission through multiple mechanisms. We explored the impact of biodiversity changes on the transmission of Amazonian leishmaniases, a group of wild zoonoses transmitted by phlebotomine sand flies (Psychodidae), which represent an important health burden in a region where biodiversity is both rich and threatened. Using molecular analyses of sand fly pools and blood‐fed dipterans, we characterized the disease system in forest sites in French Guiana undergoing different levels of human‐induced disturbance. We show that the prevalence of Leishmania parasites in sand flies correlates positively with the relative abundance of mammal species known as Leishmania reservoirs. In addition, Leishmania reservoirs tend to dominate in less diverse mammal communities, in accordance with the dilution effect hypothesis. This results in a negative relationship between Leishmania prevalence and mammal diversity. On the other hand, higher mammal diversity is associated with higher sand fly density, possibly because more diverse mammal communities harbor higher biomass and more abundant feeding resources for sand flies, although more research is needed to identify the factors that shape sand fly communities. As a consequence of these antagonistic effects, decreased mammal diversity comes with an increase of parasite prevalence in sand flies, but has no detectable impact on the density of infected sand flies. These results represent additional evidence that biodiversity changes may simultaneously dilute and amplify vector‐borne disease transmission through different mechanisms that need to be better understood before drawing generalities on the biodiversity‐disease relationship. Abstract : see also the Perspective by Taal Levi and Aimee L. Massey